A call for greater conceptual clarity in the field of mental health and psychosocial support in humanitarian settings. (8th January 2021) - Miller, K. E.; Jordans, M. J. D.; Tol, W. A.; Galappatti, A.
Abstract: Aims: When the Interagency Standing Committee (IASC) adopted the composite term mental health and psychosocial support (MHPSS) and published its guidelines for MHPSS in emergency settings in 2007, it aimed to build consensus and strengthen coordination among relevant humanitarian actors. The term MHPSS offered an inclusive tent by welcoming the different terminologies, explanatory models and intervention methods of diverse actors across several humanitarian sectors (e.g., health, protection, education, nutrition). Since its introduction, the term has become well-established within the global humanitarian system. However, it has also been critiqued for papering over substantive differences in the intervention priorities and conceptual frameworks that inform the wide range of interventions described as MHPSS. Our aims are to clarify those conceptual frameworks, to argue for their essential complementarity and to illustrate the perils of failing to adequately consider the causal models and theories of change that underlie our interventions. Methods: We describe the historical backdrop against which the term MHPSS and the IASC guidelines were developed, as well as their impact on improving relations and coordination among different aid sectors. We consider the conceptual fuzziness in the field of MHPSS and the lack of clear articulation of the different conceptual frameworks that guide interventions. We describe the explanatory models and intervention approaches of two primary frameworks within MHPSS, which we label clinical and social-environmental . Using the examples of intimate partner violence and compromised parenting in humanitarian settings, we illustrate the complementarity of these two frameworks, as well as the challenges that can arise when either framework is inappropriately applied. Results: Clinical interventions prioritise the role of intrapersonal variables, biological and/or psychological, as mediators of change in the treatment of distress. Social-environmental interventions emphasise the role of social determinants of distress and target factors in the social and material environments in order to lower distress and increase resilience in the face of adversity. Both approaches play a critical role in humanitarian settings; however, the rationale for adopting one or the other approach is commonly insufficiently articulated and should be based on a thorough assessment of causal processes at multiple levels of the social ecology. Conclusions: Greater attention to the 'why' of our intervention choices and more explicit articulation of the causal models and theories of change that underlie those decisions (i.e., the 'how'), may strengthen intervention effects and minimise the risk of applying the inappropriate framework and actions to a particular problem.